2022
DOI: 10.15252/embj.2022111268
|View full text |Cite|
|
Sign up to set email alerts
|

Stearate‐derived very long‐chain fatty acids are indispensable to tumor growth

Abstract: Reprogramming of lipid metabolism is emerging as a hallmark of cancer, yet involvement of specific fatty acids (FA) species and related enzymes in tumorigenesis remains unclear. While previous studies have focused on involvement of long‐chain fatty acids (LCFAs) including palmitate in cancer, little attention has been paid to the role of very long‐chain fatty acids (VLCFAs). Here, we show that depletion of acetyl‐CoA carboxylase (ACC1), a critical enzyme involved in the biosynthesis of fatty acids, inhibits bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Disruption of FA elongation by silencing ELOVL5 can suppress proliferation and invasion of renal cell carcinoma [ 31 ]. Moreover, VLCFA deficiency results in a marked decrease in ceramides as well as downstream glucosylceramides and sphingomyelins, which impairs mitochondrial morphology and renders cancer cells sensitive to oxidative stress and cell death [ 32 ]. Pyrimidine metabolism, one carbon pool by folate and aminoacyl-tRNA biosynthesis are tightly associated to nucleotides biosynthesis and translation, which are indispensable for rapid proliferation of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of FA elongation by silencing ELOVL5 can suppress proliferation and invasion of renal cell carcinoma [ 31 ]. Moreover, VLCFA deficiency results in a marked decrease in ceramides as well as downstream glucosylceramides and sphingomyelins, which impairs mitochondrial morphology and renders cancer cells sensitive to oxidative stress and cell death [ 32 ]. Pyrimidine metabolism, one carbon pool by folate and aminoacyl-tRNA biosynthesis are tightly associated to nucleotides biosynthesis and translation, which are indispensable for rapid proliferation of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, stearate can act as an energy source for the growth of specific cancer cells. Stearate biosynthesis II is reported to be involved in the development of certain types of cancer [ 37 ]. Although there is currently no direct link between sucrose degradation and cancer, research suggests that diets high in sugar and refined carbohydrates can lead to inflammation [ 38 ], which may increase the risk of certain types of cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subsequent analysis revealed a significant positive correlation between NDUFAB1 and fatty acid elongation (Figure 12A). Long-chain fatty acids have been strongly associated with cancer development [18,19]. CCK8 analysis indicated that knockdown of NDUFAB1 significantly reduced cell viability in both MCF-7 and MDA-MB-231 cell lines, suggesting that NDU-FAB1 may promote proliferation (Figure 12B,C).…”
Section: Critical Role Of Ndufab1 Gene In Migration and Proliferation...mentioning
confidence: 98%